(3GdefMI aj MaX GdUMIs - (3GdjGaj , UGdM efUhQ GdjGaj,J (B1268 (3g` s
(3ChdgG (B:s
(3CeG HYO (B: (3jbhd QGLi Yah QHg GdcGai UGdM Hf GdSjO eMeO efUhQ GdjGai (B: (3gPg QSGdI dWjaI hOQI efajI hVYJgG ajeG jUdM ddHOf ai MGd GdUMI s
(3BNQgG (B:s
(3NPgG HYde hGdYdje gh GdPi hGdMb CfWbJfi hdi hdgGHQG hYdi GdfHi hBdg hUMGHg Udi Edg GdYQT eGHQb SQi s
(3GdfSNI HgG MhGTs
(3gfGc Tc ai fSHI GdeNWhWGJ ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B13s
Keywords: (3GdWHs